Association of lung function and chronic obstructive pulmonary disease with American Heart Association's Life's Simple 7 cardiovascular health metrics. (October 2017) - Fan, Wenjun; Lee, Hwa; Lee, Angela; Kieu, Chi; Wong, Nathan D.
Abstract: Background: Chronic obstructive pulmonary disease (COPD) is the third leading cause of death in the U.S. There is a strong association between COPD and cardiovascular (CV) disease; however, the relation between COPD and CV health factors is not well defined. We examined the relation between lung function and CV health factors defined by American Heart Association's (AHA) Life's Simple 7 (LS7). Methods: We studied 6352 adults aged ≥20 from the National Health and Nutrition Examination Survey (NHANES) 2009–2012. Analysis of variance was used to compare mean FEV1% of predicted across levels of each LS7 metric and population attributable risk was calculated based on COPD prevalence. We also conducted linear regression and logistic regression analyses to determine the association between lung function, COPD and LS7 score. Results: Overall 19.9% of subjects were defined as having COPD. Subjects in the highest categories of the LS7 metrics had the highest mean values of FEV1% of predicted (p < 0.0001 except for total cholesterol). Current smoking and hypertension had a population attributed risk of 21.8% and 21.1% of COPD, respectively. Compared to subjects with 0 ideal health factors, the gender and ethnicity-adjusted odds (95% CI) for COPD were 0.45 (0.22–0.93), 0.22 (0.11–0.43) for those with 4 and 5–7 factors, but adjustment for age attenuated this relation. Conclusions: LS7 score is associated with lung function as well as the odds of COPD that is largely explained by age. Studies are needed to show if promotion of CV health will preserve healthy lung function. Highlights: Participants at ideal level of LS7 (except for total cholesterol) have a significant better lung function. COPD participants have a significant lower Life's Simple 7 score than non-COPD counterparts. Adjusted FEV1% of predicted were correspondingly 2% greater with 1 unit changed in LS7 score (p < 0.0001). Subjects with 5 or more ideal LS7 were 78% less likely to have COPD, but adjustment for age attenuated this relation.